2022
DOI: 10.3390/jcm11154636
|View full text |Cite
|
Sign up to set email alerts
|

Atypical 15q11.2-q13 Deletions and the Prader-Willi Phenotype

Abstract: Background: Prader-Willi syndrome (PWS) is a rare genetic disorder resulting from the lack of expression of the PWS region (locus q11-q13) on the paternally derived chromosome 15, as a result of a type I or II paternal deletion (50%), maternal uniparental disomy (43%), imprinting defect (4%) or translocation (<1%). In very rare cases, atypical deletions, smaller or larger than the typical deletion, are identified. These patients may have distinct phenotypical features and provide further information regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Huang et al also recently reported a mosaic, nonsense SNRPN variant (c.73C > T, p.R25X) found in a patient with some findings of classic PWS, although with an overall milder form of the phenotype [ 17 ]. The present study is now the fourth published patient with classic PWS findings that does not demonstrate an aberration of either an exon near the imprinting center of SNURF-SNRPN nor SNORD116 [ 15 , 17 , 18 ]. The deletion found in our patient is also unique without any overlapping deletion reported in the literature.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Huang et al also recently reported a mosaic, nonsense SNRPN variant (c.73C > T, p.R25X) found in a patient with some findings of classic PWS, although with an overall milder form of the phenotype [ 17 ]. The present study is now the fourth published patient with classic PWS findings that does not demonstrate an aberration of either an exon near the imprinting center of SNURF-SNRPN nor SNORD116 [ 15 , 17 , 18 ]. The deletion found in our patient is also unique without any overlapping deletion reported in the literature.…”
Section: Discussionmentioning
confidence: 93%
“…They describe a 6.4 kb deletion that overlaps with the imprinting center in a patient with decreased fetal movement, poor feeding, and hypotonia in infancy who developed developmental delays and obesity with small hands and feet (consistent with nonclassic PWS given that the clinical score was less than 8). In another case series ( N = 8) of atypical deletions in patients with PWS, one of the patients also had a partial deletion of SNURF-SNRPN (including the entire SNURF transcript (NM_005678.5) and exons 4–13 of SNRPN (NM_001400738.1); see Figure 2 ) that did not directly affect SNORD116 [ 18 ]. This patient had infantile hypotonia, obesity, hyperphagia, behavioral challenges (irritability), and skin-picking and did not require tube feeding as an infant; thus, this patient also did not meet enough criteria to be consistent with classic PWS.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which Prepl is downregulated is currently unknown but is apparently tissue-specific. The Snord116 cluster has been suggested to contribute to most of the neuroendocrine features observed in PWS patients (38)(39)(40). The in-silico RNA-RNA interaction prediction algorithm, IntaRNA (41), identified multiple strong interaction motifs between all 30 SNORD116 copies and PREPL mRNA (Supplementary figure 3), suggesting that these can bind and possibly post-transcriptionally stabilize PREPL mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…While several reviews have provided insights into the clinical presentations, symptoms, and molecular details of TS14 and KOS14, here we shall focus on specific snoRNAs from the 14q32.2 cluster for which some functions have been identified (Ogata & Kagami, 2016; Prasasya et al, 2020). The evidence for the involvement of imprinted snoRNAs in neurological disorders comes from a well‐studied SNORD115‐SNORD116 cluster, where a microdeletion within SNORD116 is sufficient to develop PWS phenotypes (Bieth et al, 2015; Duker et al, 2010; Grootjen et al, 2022). In addition, SNORD112 and SNORD113‐SNORD114 have shown enriched expression in placental tissue, fibroblasts, chondrocytes, and other cell types (Jorjani et al, 2016).…”
Section: Role Of Dlk1‐dio3 C/d Box Snornas In Developmental Disordersmentioning
confidence: 99%